CKAMP44: a brain-specific protein attenuating short-term synaptic plasticity in the dentate gyrus - Engelhardt, Jakob von; Mack, Volker; Sprengel, Rolf; Kavenstock, Netta; Li, Ka Wan; Stern-Bach, Yael; Smit, August B.; Seeburg, Peter H.; Monyer, Hannah (Science, 2010)
CKAMP44, identified here by a proteomic approach, is a brain-specific type I transmembrane protein that associates with AMPA receptors in synaptic spines. CKAMP44 expressed in Xenopus oocytes reduced GluA1- and A2-mediated steady-state currents, but did not affect kainate- or N-methyl- d-aspartate (NMDA) receptor-mediated currents. Mouse hippocampal CA1 pyramidal neurons expressed CKAMP44 at low abundance, and overexpression of CKAMP44 led to stronger and faster AMPA receptor desensitization, slower recovery from desensitization, and a reduction in the paired-pulse ratio of AMPA currents. By contrast, dentate gyrus granule cells exhibited strong CKAMP44 expression, and CKAMP44 knockout increased the paired-pulse ratio of AMPA currents in lateral and medial perforant path-granule cell synapses. CKAMP44 thus modulates short-term plasticity at specific excitatory synapses.